Butler County’s Kafir Corn Carnivals - Joyce Thierer (Symphony in the Flint Hills, 2014)
The history of Butler County’s Kafir Corn Carnivals
Keywords: Kafir Corn Carnival; festival; farm; dry climate; history; crop